Analisis Teras Berita pada Berita Harian Koran Radar Banten Edisi 263-264 (30 April dan 2 Mei 2025) - Muhammad Fauzan; Billgheza Alshakira Bunga; Adhi Kusuma (Pusat riset dan Inovasi Nasional, 2025)
This study focuses on the analysis of news lead styles in the Radar Banten daily newspaper editions 263-264, dated April 30 and May 2, 2025. The lead, or news angle, serves as the initial contact for readers with the news, impacting public perception based on its presentation. There are two main types of news leads: direct and indirect. Direct leads deliver critical information concisely, addressing the core elements of who, what, when, where, why, and how (5W+1H), whereas indirect leads entice readers into the story, offering hints about the content. External and internal factors, including editorial policies and media characteristics, influence the writing style. Radar Banten, a significant local newspaper in Banten, demonstrates flexibility in utilizing both types of leads, catering to its audience's informational needs. The research employs a qualitative descriptive approach, analyzing selected news pieces to understand their structure and writing techniques, ultimately highlighting the effective composition necessary for engaging reporting.